Molecular Docking Study of 3-Amino-2-Phenylquinazoline-4(3H)-One Derivative as A Potential COX-2 Selective Analgesic Candidate - Naura Salsabila Nadhifa; Luthfi Ahmad Muchlashi (Brawijaya University, 2024)
Background: Quinazoline is a group of alkaloid compounds found in several plant and animal families, such as plants in the Rutaceae family. Non-selective COX-2 inhibitors, while effective analgesics, may also inhibit COX-1 in the gastrointestinal tract, potentially disrupting protective mucus production. This research aims to assess the potential of the derivative compound 3-Amino-2-Phenylquinazoline-4(3H)-One as an analgesic agent through molecular docking. The selection of test compounds was conducted using the Topliss Tree method. The potency of the compounds was assessed based on rerank scores and interactions with amino acids in COX-2 (PDB ID 1PXX) and COX-1 (PDB ID 1EQG). The findings suggest that compound 14cpq may exhibit selective COX-2 inhibitory activity. This is supported by its lower rerank score with COX-2 (-85.2374 arb. units) compared to COX-1 (-63.9889 arb. units), as well as its interactions with amino acids Ser1530 and Met1522 within the COX-2 binding site, similar to sodium diclofenac. Furthermore, 14cpq displays distinct interaction patterns with COX-1 compared to ibuprofen, reinforcing its potential selectivity for COX-2. However, further research is required to ascertain the effectiveness of these compound as selective COX-2 analgesics. Keywords: 3-amino-2-phenylquinazoline-4(3H)-one derivatives; analgesic; molecular docking